Potentiation of antimicrobial photodynamic inactivation by inorganic salts - Hamblin, Michael R (Expert Rev Anti Infect Ther, 2017)
INTRODUCTION: Antimicrobial photodynamic inactivation (aPDI) involves the use of non-toxic dyes excited with visible light to produce reactive oxygen species (ROS) that can destroy all classes of microorganisms including bacteria, fungi, parasites, and viruses. Selectivity of killing microbes over host mammalian cells allows this approach (antimicrobial photodynamic therapy, aPDT) to be used in vivo as an alternative therapeutic approach for localized infections especially those that are drug-resistant. AREAS COVERED: We have discovered that aPDI can be potentiated (up to 6 logs of extra killing) by the addition of simple inorganic salts. The most powerful and versatile salt is potassium iodide, but potassium bromide, sodium thiocyanate, sodium azide and sodium nitrite also show potentiation. The mechanism of potentiation with iodide is likely to be singlet oxygen addition to iodide to form iodine radicals, hydrogen peroxide and molecular iodine. Another mechanism involves two-electron oxidation of iodide/bromide to form hypohalites. A third mechanism involves a one-electron oxidation of azide anion to form azide radical. EXPERT COMMENTARY: The addition of iodide has been shown to improve the performance of aPDT in several animal models of localized infection. KI is non-toxic and is an approved drug for antifungal therapy, so its transition to clinical use in aPDT should be straightforward.